Colorectal Cancer Diagnosis Using Enzyme‐Sensitive Ratiometric Fluorescence Dye and Antibody–Quantum Dot Conjugates for Multiplexed Detection. (22nd November 2017) - Park, Youngrong; Ryu, Yeon‐Mi; Wang, Taejun; Jung, Yebin; Kim, Sohee; Hwang, Sekyu; Park, Joonhyuck; Bae, Dong‐Jun; Kim, Jaeil; Moon, Heejo; Lim, Hyun‐Suk; Kim, Sang‐Yeob; et al.
Abstract: A rapid and accurate molecular fluorescence imaging technique will greatly reduce cancer mortality by overcoming the detection limit of the naked eye in colonoscopy. Two imaging probes are reported that can be co‐used for colonoscopic diagnosis: a fluorescent molecular probe, cresyl violet–glutamic acid derivative, that ratiometrically switches between two fluorescent colors in response to the enzyme activity of λ‐glutamyltranspeptidase and an antibody quantum dot probe that is a conjugate of biocompatible AgInS2 quantum dot with matrix metalloproteinase 14 antibodies. Validity of the probes is confirmed using human colon cancer cell lines, ex vivo mouse model tissues, and patient tumor colon tissues in which the tumor lesions are well‐visualized in less than five minutes. Co‐application of the two probes onto fresh colon tissues affords accurate visualization of carcinomas and also hyperplasia and adenoma regions. Fresh human colon adenoma tissues are also valuated, where the two probes show complementary diagnoses of cancer. Two‐photon microscopy shows the time‐dependent depth profiles of the two probes. Both rapidly permeate and populate most at 10–20 µm from the surface. Extensive toxicity studies are performed for the two probes at cellular level and also at the organ level using a small animal model. Abstract : A ratiometric fluorescent probe that responds to λ‐glutamyltranspeptidase activity is developed and co‐used with an antibody–quantum dot conjugate probe, which demonstrates the potential for endoscopic early colon cancer diagnosis by multiplexed and complementary detection of colorectal tumors and precancerous regions such as adenoma and hyperplasia.